Two-Stage Primary Arthroplasty of Native Hips and Knees That Had Previously Failed Treatment for Septic Arthritis: A Single-Center Experience - Kyle N. Kunze, BS; Alexander J Sadauskas, MD; Benjamin Kerzner, BS; Brett R. Levine, MD, MS (Arthroplasty Today, 2020)
Background: Patients with a history of degenerative joint disease secondary to an acute or remote episode of septic arthritis of the native knee or hip present a unique challenge for the orthopaedic surgeon. This study describes our experience with two-stage primary arthroplasty for such patients. Methods: We reviewed 42 patients with a history of septic arthritis treated with two-stage primary arthroplasty between 2008 and 2018. Patients were evaluated using modified Harris Hip Score, Knee Society Score (KSS), and KSS functional component (KSSF). Paired t-tests were used to compare changes for continuous variables within cohorts. Multivariate linear and logistic regression models were constructed to determine predictors of outcomes and complications. Results: At a mean of 3.3-year follow-up, there were 14 (33.3%) complications and the infection cure rate was 95.2%. On average, patients improved in the modified Harris Hip Score (42.9 ± 11.8 vs 83.3 ± 11.1, P < .001), KSS (35.9 ± 16.9 vs 80.1 ± 16.6, P < .001), KSSF (38.0 ± 15.1 vs 71.5 ± 24.0, P < .001), knee flexion (90.9 ± 14.9 vs 100.5 ± 17.1), and hip flexion (73.8 ± 21.2 vs 102.1 ± 11.8, P < .001). Age (β: −0.78, P = .004) was independently associated with lower Harris Hip Score in the hip cohort. There were no independent predictors of the KSS or KSSF. The erythrocyte sedimentation rate (odds ratio: 1.07, P = .043) and C-reactive protein (odds ratio: 1.43, P = .018) at stage 2 were independently associated with a higher likelihood of complications at the final follow-up. Conclusions: Patients with a history of native septic arthritis of the hip and knee, and secondary end-stage degenerative joint disease, showed significant postoperative improvements and a high rate of complications after two-stage primary total joint arthroplasty. Despite improvements, some patients may necessitate a third operation because of the incidence of reinfection and spacer exchange. This information should be used to counsel patients who present with this challenging clinical scenario.